Modes of commuting to school among 5th and 6th grade schoolchildren - Souza, Sérgio (2019)
Active commuting (walking/cycling) is seen as a strategy to promote active behaviors in children’s daily school life. This study aimed to analyze the modes of commuting and perceptions of children in relation to the possibility of active commuting to school according to sex. Overall, 101 students (M=11.39/SD=1.22) enrolled in the 5th and 6th grades from two public elementary schools in the state of Maranhão, Brazil, participated in this study. Data were collected through a questionnaire administered to students. The results showed that 21.8% of respondents had active commuting (19.8% on foot / 2% bicycle), without statistically significant differences; however, boys were more predisposed to walking and cycling in relation to girls. As positive justifications, respondents evidenced the ‘home-school proximity’ and ‘fun/ pleasure’ provided during the journey, and ‘distance’ and ‘traffic / insecurity’ as barriers to the possibility of walking or cycling to school.